Maxillofacial Surgery and Craniofacial Deformity - Practices and Updates 2020
DOI: 10.5772/intechopen.81937
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Disorders of the Temporomandibular Joint (Internal Disorders)

Abstract: There are many factors that can cause damage to the temporomandibular joint (TMJ) structures or impair normal functional relationships between condyle, disc and eminence. The main symptoms associated with TMJ dysfunction are pain, limited mobility of the mandible, spasticity of the masticatory muscles and sound that is produced in the joint during mandibular movement. Pain originates from nociceptors located in soft tissue of the joint. If the soft tissue structures are not in inflammation, the pain is sharp, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…The constant excessive pressure in that zone can lead to perforation of the disc. 8 Trismus is one of the classical manifestations of OSMF due to accumulation of inelastic fibrous tissue in the juxta epithelial region of oral mucosa with associated muscle degeneration. Progressive restriction in movement of the joint secondary to OSMF and a deficient functional stimulation of TMJ leads to reduced efficiency of the temporomandibular joint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The constant excessive pressure in that zone can lead to perforation of the disc. 8 Trismus is one of the classical manifestations of OSMF due to accumulation of inelastic fibrous tissue in the juxta epithelial region of oral mucosa with associated muscle degeneration. Progressive restriction in movement of the joint secondary to OSMF and a deficient functional stimulation of TMJ leads to reduced efficiency of the temporomandibular joint.…”
Section: Discussionmentioning
confidence: 99%
“…According to another study, it has been observed that there are bony changes in terms of generalised osteoporosis of cancellous and cortical bone due to prolonged immobilisation of rat knee joints. 8,15 Some investigators evaluated changes in TMJ anatomy through MRI in patients with disc displacement and found a substantive change and a direct correlation. 16 A definite correlation to structural changes with duration of reduced mouth opening was noted in all the cases but statistically significant results were not obtained due to small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…In conditions of closed-mouth position and teeth contact, if there is an extreme and long load, it could cause the thinning of the disc in the central band [59]. Moreover, cases of displacement could also lead to thinning of the posterior band [60].…”
Section: Disc Structural Changesmentioning
confidence: 99%